Pengaruh Literasi Keuangan dan Kemampuan Finansial Terhadap Minat Mahasiswa dalam Investasi Saham Syariah - Badrut Tamam, Ahmad; M. Ihsanuddin (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2023)
The purpose of this study was to determine the effect of financial literacy and financial ability on Islamic stock investment interest in Islamic economics students at IAI TABAH Lamongan. Researchers want to see the factors that influence the investment interest of a student who has gained knowledge about investment or the capital market. This research uses quantitative methods while non-probability sampling technique is saturated sampling type. Primary data used in this study by distributing questionnaires totaling 47 respondents and processed using SPSS Statistics 26. Based on the results of the analysis, it is shown that financial literacy and financial ability have a significant effect on the interest in Islamic stock investment in Islamic economics students at IAI TABAH Lamongan. Keywords; Financial Literacy, Financial Ability, Investment Interest